Is the largest African penguin colony in South Africa influencing local ocean productivity?. Issue 4 (2nd October 2021) - Passuni, G; Human, LRD; Riddick, SN; Pattrick, P; Bizani, M; Deyzel, SHP; Strydom, NA; Bornman, TG; Pichegru, L
Abstract : In coastal waters, nutrient supplies originate principally from allochthonous sources, such as inputs from rivers, estuaries or oceanic waters. Recently, it has been suggested that marine life contributes to the nutrient load, with penguin colonies being the largest contributor worldwide. This study aimed to quantify the nitrogen (N) and phosphorus (P) produced by the largest colony of African penguins Spheniscus demersus, which is located in South Africa, using a bioenergetics model (GUANO). We modelled the fate of N excreted and measured potential effects on the physicochemical parameters of the waters surrounding St Croix Island, Algoa Bay, as well as on local primary and secondary productivity. A total of 58.66 (SD 14.99) tonnes (t) of N and 4.35 (SD 1.20) t of P were estimated to be produced by penguins annually, a magnitude comparable to that exported by permanently open estuaries in Algoa Bay. However, only 8% of penguin-produced N washed into the ocean (after moderate to heavy precipitation) as total ammoniacal N, while 58% of N was excreted as volatilised ammonia. Consequently, penguin excreta appeared to have limited influence on productivity in the waters surrounding St Croix Island, at both proximate (200 m) and distant (2 km) locations. Additional experiments should confirm whether the input of N excretion in coastal waters was too ephemeral to be detected at the monthly scale, or whether the effects were restricted to intertidal communities. Regardless, sources of nutrients other than penguins, such as coastal upwelling and runoff, are likely to have a greater influence on the physicochemical dynamics and productivity of Algoa Bay nearshore waters.